Interfirm networks theory, strategy, and behavior - Baxter, Roger, 1944-; Woodside, Arch G. (Advances in business marketing & purchasing ;, 2011)
Nearly all business-to-business firms interact and have contractual relationships with upstream, downstream and parallel operating enterprises. How firms design and implement these relationships effectively, overcome poorly performing network linkages, and manage change in interfirm networks are the major topics that Volume 17 covers. The five papers in Volume 17 report new theory and in-depth descriptions of interfirm network behavior. Each paper includes extensive reviews of the relevant literature on interfirm network behavior as well as data analysis using empirical positivistic and/or case study research methods.More than 150 figures and tables support the discussion of findings.